'If You're Down With a Gang Inside, You Can Lead a Nice Life': Prison Gangs in the Age of Austerity. (April 2020) - Maitra, Dev Rup
In many countries, there has been growing academic attention towards the activities of street and prison gang members. However, while much of the American literature explores the experiences of prison gang members, such investigation has been notably absent in the English context. This article seeks to address this deficit in the literature. Through gathering data from interviews with active prison gang members, it shows how reduced staffing levels in English prisons has led to an increasingly 'ungovernable' prison space. This, in turn, has led to an increase in levels of gang membership. Most notably, the high numbers of street gangs 'imported' into prisons has had the unintended effect of creating several 'in prison' gangs, which form for the first time in prison, with their members seeking protecting from more established gangs. This proliferation of gangs has had a significant impact on rates of in-prison violence, and how prisons are managed.